The Geographical Impact of the Provinces of Cyrenaica, Tripolitania and Fezzan on the Aspects of Economic and Cultural Life ( 3-8 Hijrae / 9-14 C.E.) (Journal of Human Sciences, 2022)
The geography of the regions of Cyrenaica, Tripolitania  and Fezzan has been considered a link between the Libyan territories , as their lands represented a continuous geographical area that the nature unified in spite of their political dependencies throughout history.What confirms this fact is the Libyan coast which linked  the regions of  Cyrenaica and Tripolitania , and the interior desert (Fezzan province)  which linked the north to the south due to the presence of  trade routes.This interdependence led to the enrichment of economic and cultural life in the three regions , which in turn was represented in the diversity of agricultural crops as a result of the appropriate climatic conditions , such as soil fertility , abundance of water , a temperate climate , as well as the prosperity of industry as a result of the abundance of raw materials.The second manifestation of this richness was trade which contributed to the distribution of  agricultural and industrial  products , which led to the spread of  markets and commercial centers. It also led to creation of scientific activity in the three regions , represented in the enrichment of mosques , schools  and  corridors that gave birth many scientists who made quite a number of scientific works.